Conversion of Lignocellulosic Biomass to Fuel Ethanol - A Brief Review. - Lim, Koon Ong (2004)

(untitled)
The paper provides a brief review of the conversion of lignocellulosic biomass to fuel ethanol. " The various steps {n. the conversion process are discussed and some information on the potential of the –conversion process are also provided.